Alouatta guariba clamitans Cabrera, 1940: a new southern limit for the species and for Neotropical primates - Printes, Rodrigo C.; Liesenfeld, Marcus V. A.; Jerusalinsky, Leandro (Neotropical Primates, 2001)
No abstract